INCOMPRESSIBLE WATER-ENTRY PROBLEMS AT SMALL DEADRISE ANGLES - Howison, S; Ockendon, J; Wilson, S (1991)
Summarizes and extends some mathematical results for a model for a class of water entry problems characterized by the geometrical property that the impacting body is nearly parallel to the undisturbed water surface and that the impact is so rapid that gravity can be neglected. Explicit solutions for the pressure distributions are given in the case of two-dimensional flow and a variational formulation is described which provides a simple numerical algorithm for three-dimensional flows. Poses some open questions concerning the well-posedness and physical relevance of the model for exit problems or when there is an air gap between the impacting body and the water. (A)